PENGARUH DUKUNGAN KELUARGA TERHADAP KESEHATAN FISIK LANSIA DI DUSUN III DESA HUTARAO KECAMATAN BANDAR PULAU KABUPATEN ASAHAN TAHUN 2014 - Sianturi, Efendi (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2019)
The elderly is seen as a group of people who are at risk of experiencing health problems are complex and progressive. One of the many problems that arise in the nursing group is social disorder because many things affect this kind of support group members of the family and the environment. Penilitian goal was to determine the effect of family support on the physical health of the elderly in the village of Dusun III Hutarao shavings Airport District Island District in 2014. This research uses analytical design with a cross-sectional design with Chi-Square Test to determine the effect of family support on the physical health of the elderly in the village of Dusun III Hutarao Island County Airport District shavings. The population is elderly and samples obtained 37 elderly aged 60 years and older who are still able to move. The result showed that the majority of informational support in less categories that affect the physical health of the elderly with a value of p = 0.001, which means there is a connection informational support to the physical health of the elderly. On the support of a majority vote by both categories of the physical health of the elderly with p = 0.0810 which means it does not influence the assessment of physical health support elderly. On the support of the majority of the categories of emotional support were less influence on the physical health of the elderly with a value of p = 0.004, which means there is a relationship between emotional support to the physical health of the elderly. In the category of family support mayorita obtained either with p = 0.026, which means there is the influence of family support on the physical health of the elderly. Research goal should be advised of the educational institutions in order to add material about the physical health of family support for the elderly and the results can be used as a reference for further research while for elderly people who have to pay more attention or providing support to the elderly so that the physical health of the elderly can be maintained better